Risk Aversion and Arbitrage - GREEN, RICHARD C.; SRIVASTAVA, SANJAY (Journal of Finance, 1985)
ABSTRACT This paper characterizes conditions under which asset returns and consumption are consistent with risk‐averse preferences. It is shown that risk aversion is equivalent to “zero arbitrage” on a transformation of the payoff space. The implicit state prices which are dual to this no‐arbitrage condition can be interpreted as prices of “pure consumption hedges.” This zero‐arbitrage restriction implies the usual restrictions associated with nonsatiation. The analysis holds in both complete and incomplete market settings.